Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12894-018-0358-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary synovial sarcoma of the kidney: a case report of complete pathological response at a Lebanese tertiary care center

Abstract: BackgroundPrimary synovial sarcoma of the kidney is a rare type of soft tissue sarcoma. Its presenting features can resemble those of other renal tumors; rendering its early diagnosis, a dilemma. Several cases of renal synovial sarcoma have been reported in the literature with varying treatment options and outcomes. This article describes a rare case of primary renal synovial sarcoma and reviews all cases in the literature.Case presentationA 26-year-old male presented with flank pain and hematuria. Initially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Partial response was shown after six courses of treatment. Chediak et al reported a case where the patient had a complete pathological response after being given adjuvant doxorubicin and ifosfamide [12] . Park et al also reported a patient who was given six courses of this chemotherapy regimen with complete remission [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Partial response was shown after six courses of treatment. Chediak et al reported a case where the patient had a complete pathological response after being given adjuvant doxorubicin and ifosfamide [12] . Park et al also reported a patient who was given six courses of this chemotherapy regimen with complete remission [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Cases of intraprostatic synovial sarcoma have also been reported in the literature. 7 10 The overall prognosis of primary metastatic synovial sarcoma remains poor, with a metastases rate of 25%, and a 48% rate of recurrence. 11 , 12 The standard approach to treating synovial sarcoma is wide surgical excision combined with radiotherapy, with or without (neo)adjuvant chemotherapy, as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLE1 antibody can also be used as an important tissue factor to distinguish PRSS from other sarcomas. Studies by Mishra et al have shown that TLE1 is more specific and sensitive to synovial sarcomas than any immunohistochemical factor[11,12]. Molecular biology is also providing further confirmation that t(X;18) translocation can lead to syt-ssx fusion, and SYT rearrangement has become the gold standard for PRSS diagnosis[4].…”
Section: Discussionmentioning
confidence: 99%